Paradigm shift: Malaysia's development plans - Rahimah A. Aziz, (Universiti Kebangsaan Malaysia, 1996)
This artical re-examinies Malaysia's development experience conducted through the process of planned change and demonstrates the paradigm shift that occurs in its development planning. Basically, there are three orientation changes in Malaysia's development planning. However, the most fundamental change in its policy orientation. The discussion will look into the underlying development paradigms of Malaysia's development plan to show when the shift took place, why it happened and the factors leading to the shift. This paradigm shift is especially clearly indicated in the Seventh Malaysia Plan (1996-2000).